Al-Risalah fi Al-Qur’an - Shohibul Adib (Al-Riwayah : Jurnal Kependidikan, 2019)
One of the miracles and blessings bestowed upon the prophet Muhammad Peace Be Upon Him (PBUH) is the revelation of Qur'an. Almighty Allah bestows the Quran to show his love and treatise (risālah) at the same time not only to the prophet, but also to the entire humanity. Treatise takes part as the guidance maintaining the correctness in the deed and faith of the human. However, the discussion in this exploration is being narrowed by having several questions in mind such as: (1) How the treatise is understood? (2) How the treatise is formed in the Qur'an? (3) What is the role of treatise in human life? The discussion makes it clear that the word Al-risālah appears ten times delivering the idea closely related to the prophets and messengers of Allah The Almighty. It is referring to the responsibility that Allah gives to His prophets and messengers. Also, they got rejection and denial when delivering the message from Allah especially from the leaders in the era. Further, the treatise from Allah The Almighty has already settled down and controlled the way of human living in this world.